Standards of suitability for the management of chronic obstructive respiratory diseases - Sanguinetti, Claudio M; Ambrosino, Nicolino; Andò, Filippo; De Benedetto, Fernando; Donner, Claudio F; Nardini, Stefano; Polverino, Mario; Torchio, Roberto; Vagheggini, Guido; Visconti, Alberto (Multidisciplinary Respiratory Medicine, 2014)
Background Chronic Obstructive Pulmonary Disease (COPD) ranks third as cause of mortality and disability-adjusted life years (DALY) worldwide and also in Italy it imposes a huge health, social and economic load. Early symptoms of COPD are often disregarded by patients and physicians, spirometry is underutilized, and the diagnosis is delayed till the disease has reached a distinct severity level. Despite the availability of various guidelines, the behavior of health workers involved in the management of COPD is still rather unlike. These considerations are the reason why in October 2013 AIMAR (Interdisciplinary Scientific Association for Research in Lung Disease) devised and organized a “Third Consensus Conference”, aimed at pointing out the standards of suitability for COPD management. In this context three important topics of discussion were identified: early and more widespread diagnosis, management of acute and subacute phases, long-term assistance to chronic patients. Methods The procedure recommended by the Italian Health Superior Institute (ISS) for Consensus Conferences organization was applied. The Conference was structured in three sessions, each dealing with one of the above mentioned topics and including a short update of the subject-matter and presentation, discussion and voting of some statements with a choice ranging from total agreement to total disagreement or no knowledge. The results of voting were eventually recorded in the document, reviewed by an independent jury, that forms the substance of this paper. Results The essential role of spirometry, the need for distinguish between different COPD phenotypes, and the obligatoriness to base on the blood gas analysis findings the long-term oxygen therapy, were largely agreed, as well as the need for interventions aimed at decreasing the rate of acute exacerbations. More specific topics like the use of noninvasive ventilation, recognizing the factors affecting outcome and mortality, the choice of pharmacological and non pharmacological treatments in COPD patients led to lively discussing, but they did not always reach the total agreement, probably because of insufficient familiarity with these problems and of diversities in organization and instruments availability. The chronic respiratory assistance was treated with particular regard to smoking cessation, whose implementation is still insufficient. Many doubts rose due to uncertainty, lack of ability and standardization of procedures, insufficient institutional support, and difficulties to realize a network for assistance to chronic patients. Conclusions The results of this Third Consensus Conference revealed some certainties and many doubts and diversities of view also on topics whose importance is well demonstrated in scientific literature. Thus, there is still a long distance to cover before reaching a suitable standardization of COPD management and such situation urges the need for improving not only the health professional’s operativeness but also the organizational support by competent institutions. In this context some initiatives organized by AIMAR in cooperation with other respiratory scientific societies and patients’ associations are going on.